2014
DOI: 10.1039/c4cp03906h
|View full text |Cite
|
Sign up to set email alerts
|

Protection of DNA against low-energy electrons by amino acids: a first-principles molecular dynamics study

Abstract: Using first-principles molecular dynamics simulations, we have investigated the notion that amino acids can play a protective role when DNA is exposed to excess electrons produced by ionizing radiation. In this study we focus on the interaction of glycine with the DNA nucleobase thymine. We studied thymineglycine dimers and a condensed phase model consisting of one thymine molecule solvated in amorphous glycine. Our results show that the amino acid acts as a protective agent for the nucleobase in two ways.If t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 43 publications
(78 reference statements)
1
29
0
Order By: Relevance
“…Consequently, raising the free-energy barrier associated with strand breaks, prompted by these mechanisms, can halt further reactions of the excess electron within the strand of DNA, for instance, transferring the electron to the backbone which leads to induce a strand break in DNA. Increasing the ratio of amino acid to nucleic acid will enhance the protecting role of amino acids, and accordingly will decrease the induction of DNA strand breaks by LEEs, as shown experimentally [137,139].…”
Section: Lees Interaction With Protein Building Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, raising the free-energy barrier associated with strand breaks, prompted by these mechanisms, can halt further reactions of the excess electron within the strand of DNA, for instance, transferring the electron to the backbone which leads to induce a strand break in DNA. Increasing the ratio of amino acid to nucleic acid will enhance the protecting role of amino acids, and accordingly will decrease the induction of DNA strand breaks by LEEs, as shown experimentally [137,139].…”
Section: Lees Interaction With Protein Building Blocksmentioning
confidence: 99%
“…Furthermore, by studying via first-principles molecular dynamics simulations a model system composed of thymine and glycine, Kohanoff et al [139] recently investigated the protection of DNA by amino acids against the effects of LEEs. They considered thymine-glycine dimers and a condensed-phase model consisting of one thymine molecule solvated in amorphous glycine.…”
Section: Lees Interaction With Protein Building Blocksmentioning
confidence: 99%
“…The most popular multi‐level approach is QM/MM method, where the solute is treated using QM, and the surrounding water molecules are treated with molecular mechanics (MM). A limited number of QM/MM based explicit solvation studies on the electron attachment to the genetic material has been reported in recent times. However, they are mostly restricted to nucleobases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition the hydrogen-bonding interactions may play an essential role in quenching SSB through the stabilization of the anionic species. These hypotheses were successively tested via FPMD simulations of a single thymine in a bath of 32 glycine molecules instead of water [147]. These were fully quantum simulations at the DFT-PBE level and TZVP-MOLOPT basis set.…”
Section: Amino Acidsmentioning
confidence: 99%